The Feminist Critique of Art History - Gouma-Peterson, Thalia; Mathews, Patricia (The Art Bulletin, 1987)
Art criticism and art history from a feminist perspective are recent phenomena, emerging only during the last fifteen years. They have, in their short history, moved from a first generation in which "the condition and experience of being female" was emphasized, to a second generation, beginning in the late 1970s, influenced by feminist criticism in other disciplines and offering a more complex critique of both art and culture through an investigation of the production and evaluation of art and the role of the artist. In this survey, we propose, first, to outline the history of feminist art and art history, then to discuss the interrelated themes in each, and, finally, in the concluding and pivotal sections (IV and V), to discuss various feminist art-critical and art-historical methodologies.
Number: 3
Keywords: 1900-1999; approches et analyses; art moderne; artistes féministes; arts; corps; cours; critique d'art; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; maternité; patriarcat; premier cycle; périodes historiques; représentation; sexisme; sexualité; systèmes d'oppressions; thématiques

L'avant-garde au feminin: Moscou, Saint-Petersbourg, Paris : 1907-1930 - Marcadé, Jean-Claude; Marcade, Valentine (Artcurial, 1983)
Paris, Artcurial, 1983, broché sous couverture illustrée, 64 pp., (27,5 x 21 cm). Exposition mai-juillet 1983. Importante illustration couleur et noir et blanc (reproductions et photographies). Biographie sommaire autour des artistes :Sonia DELAUNAY, Alexandra EXTER, Marie VASSILIEFF, Marianne WEREFKIN, Natalia GONTCHAROVA, Lioubov POPOVA, Nadiejda OUDALTSOVA, Olga ROZANOVA, Nina KOGAN, Vera PESTEL, Vera ERMOLAIEVA, Xenia ENDER, etc.
Section: 64 p. : ill. (certaines en coul.)
Keywords: 1900-1999; 1910-1919; 1920-1929; approches et analyses; art moderne; arts; cours; discipline; discours dominant; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; moscou; paris; premier cycle; périodes historiques; russie; régions géographiques; saint-petersbourg; sexisme; systèmes d'oppressions; thématiques